2014
DOI: 10.1371/journal.pone.0110016
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Transitioning and Change of Self-Reported Sexual Orientation

Abstract: ObjectiveSexual orientation is usually considered to be determined in early life and stable in the course of adulthood. In contrast, some transgender individuals report a change in sexual orientation. A common reason for this phenomenon is not known.MethodsWe included 115 transsexual persons (70 male-to-female “MtF” and 45 female-to-male “FtM”) patients from our endocrine outpatient clinic, who completed a questionnaire, retrospectively evaluating the history of their gender transition phase. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…29,30 Some transgender individuals change sexual orientation at the time of their physical transformation. 31 Transgender individuals also have a wide range of sexual attraction ranging from men only, women only, both men and women, neither, all genders (i.e., pansexual), or specifically other transgender men and women. 32,33 Classifying patients into only three categories, as done in our analysis, and during one period of time can be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Some transgender individuals change sexual orientation at the time of their physical transformation. 31 Transgender individuals also have a wide range of sexual attraction ranging from men only, women only, both men and women, neither, all genders (i.e., pansexual), or specifically other transgender men and women. 32,33 Classifying patients into only three categories, as done in our analysis, and during one period of time can be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual orientation may affect transgender identity development and vice versa (58). For example, transgender men attracted to women may identify as lesbian before coming out as transgender, while other transgender men or women may not explore their attractions toward men until after transition (59, 24, 60, 61). Vulnerabilities and sexual health needs may differ by sexual orientation (62, 63).…”
Section: Sexual and Reproductive Healthmentioning
confidence: 99%
“…However, only two studies have compared trans feminine individuals with trans masculine individuals in the same study. A U.S. community-based study found greater sexual fluidity among trans masculine individuals compared to trans feminine individuals (Katz-Wise, 2015a), and a German study using a clinical sample of transgender individuals found no significant difference in prevalence of sexual fluidity between trans feminine and trans masculine individuals (Auer et al, 2014). …”
Section: Introductionmentioning
confidence: 97%
“…Research on sexual fluidity in cisgender individuals has indicated that changes occur more frequently among sexual minority individuals compared to heterosexual individuals (Ott, Corliss, Wypij, Rosario, & Austin, 2011; Savin-Williams, Joyner, & Rieger, 2012), and some studies have found that sexual minority women and men are equally likely to report experiencing sexual fluidity (Katz-Wise, 2014; Kinnish, Strassberg, & Turner, 2005; Ott et al, 2011). Sexual fluidity has been documented among both trans feminine (male-to-female; MTF) individuals and trans masculine (female-to-male; FTM) individuals (Auer, Fuss, Höhne, Stalla, & Sievers, 2014; Coleman, Bockting, & Gooren, 1993; Daskalos, 1998; Katz-Wise, 2015a; Meier, Pardo, Labuski, & Babcock, 2013). However, only two studies have compared trans feminine individuals with trans masculine individuals in the same study.…”
Section: Introductionmentioning
confidence: 99%